Identification and Application of DNA Microsatellite Markers for the Genetic Characterisation of the Green-Lipped Mussel, Perna Viridis - Ong, Lily Chin Chin (2007)
A total of 264 microsatellite sequences were successfully isolated from P. viridis by using 5’ anchored PCR technique and 109 primer pairs were designed to amplify these repeat regions. Of these, 19 were found to be polymorphic and were used to analyse levels of genetic variation for 10 populations of P. viridis collected all over the Peninsular Malaysia. The populations involved in this study included Pulau Aman in Penang, Tanjung Rhu in Kedah, Bagan Tiang in Perak, Pulau Ketam in Selangor, Muar, Parit Jawa, Pantai Lido and Kampung Pasir Puteh in Johore, and Kuala Pontian and Nenasi in Pahang. The number of alleles per locus ranged from 2 to 7 with an average of 3.1. The highest value of observed heterozygosity was 0.208 (Pulau Ketam) and the lowest value was 0.144 (Pulau Aman). Heterozygote deficiencies were observed across all the ten populations. The Wahlund effect, inbreeding and null alleles are believed to be the most likely factors for the occurrence of heterozygote deficiencies in this study. Characterisation of the populations revealed that local populations of P. viridis in Peninsular Malaysia were genetically similar enough to be used as a biomonitoring agent for heavy metal contamination in the Straits of Malacca. Cluster analysis grouped the P. viridis populations according to their geographical distribution with the exception of Parit Jawa. The analysis also revealed that P. viridis from the northern parts of Peninsular Malaysia (Tanjung Rhu and Pulau Aman) were found to be the most distant populations among the populations of mussels investigated and P. viridis from the eastern part of Peninsular Malaysia (Kuala Pontian and Nenasi) were closer to the central and southern populations than to the northern populations.